Anomalous thermal transport in metallic transition-metal nitrides originated from strong electron–phonon interactions. (December 2020) - Li, S.; Wang, A.; Hu, Y.; Gu, X.; Tong, Z.; Bao, H.
Abstract: Metallic transition-metal nitrides (TMNs) are promising conductive ceramics for many applications, whose thermal transport is of great importance. In this article, thermal transport properties of TiN and HfN are investigated through a first-principle-based method with rigorous consideration of phonon and electron scatterings. It is found metallic TiN and HfN hold different thermal transport behaviors compared with common metals and non-metallic TMNs. Without phonon–electron scatterings, they could have extremely large phonon thermal conductivity. The phonon thermal conductivity is reduced by two orders of magnitude as the phonon–electron scatterings are considered. The nesting Fermi surfaces existing in both TiN and HfN are the main reason for the strong electron–phonon interactions. Such an effect also induces the unusual temperature-independent behavior of phonon thermal conductivity. The phonon component takes a large ratio in total thermal conductivity, as 29% for TiN and 26% for HfN at 300 K. The results for thin films are also presented, and it is shown that the phonon thermal conductivity can be efficiently suppressed by size. Our findings can provide a deeper understanding on the thermal transport in metallic TMNs as well as electron and phonon heat conduction in metals. Highlights: Thermal transport properties of both phonon and electron in metallic transition-metal nitrides are analyzed by solving BTEs. TiN and HfN hold extremely large intrinsic phonon thermal conductivities, which can be reduced by two orders of magnitude as phonon–isotope and phonon–electron scatterings are considered. The phonon thermal conductivities of TiN and HfN are almost temperature-independent, and they take a large proportion in total thermal conductivities. The size effect is relatively weak in electron thermal conductivity, while it is strong in phonon thermal conductivity.